A conceptual approach to the tourist value co-creation: dimensions, antecedents and consequences. - Carvalho, Pedro; Díaz-Méndez, Montserrat; Quero-Gervilla, María José; Saren, Michael (Varna University of Management, 2023)
In the last decades, several studies related to the Service-Dominant Logic approach were carried out, where the tourism industry is not an exception. As such, multiple works associated with this research stream have been developed, with a special focus on the tourist value co-creation. This article presents a conceptual model that aims to aggregate the various dimensions of customer value co-creation with its antecedent and consequent factors in the tourism industry. On the other hand, it proposes practical implications for the tourist organizations building on conceptual contributions. Thus, this article reveals the importance of other constructs of tourist value cocreation which surpass the behavioral dimension of the customer, namely, attitude, significance and recognition. Furthermore, this study systematizes the multiplicity of antecedent and consequent factors, recognizing that they may be grouped into factors associated to the company as well as to the customer.
Keywords: Turismo; Economía; Customer co-creation; Value co-creation; Tourism marketing; Literature review; Service dominant logic